Confidence in the efficacy of routine vaccines after the COVID-19 pandemic: a cross-sectional web-based study - Areej M. Zubaid; Maha T. Alhamdi; Noor I. Al-Harthi; Khulood M. Al-Harthi; Razan A. AlQarni; Yassmin M. Shebany; Ahmed Ibrahim Fathelrahman; Sayed F. Abdelwahab (BMC Public Health)
Abstract Background There is limited data that assessed the changes in public confidence in routine childhood and adult vaccines after Corona Virus Disease-2019 (COVID-19) pandemic. We, therefore, assessed these changes and the reasons; if any; for these changes and measured the impact of COVID-19 on peoples’ thoughts regarding routine vaccinations in Saudi Arabia. Methods We undertook a cross-sectional online study in Saudi Arabia from November 2023 to April 2024. Participation was voluntary for those above 18 years and lived in Saudi Arabia. The study tool was an online self-administered questionnaire. Data gathered were analyzed using the SPSS version 25 software. Results A total of 1217 Saudi Arabian participants were enrolled. Among the total participants, only 32.4% (n = 394) participants were males. Most of the participants (55%, n = 679) were from the western region and were married (56.9%, n = 693). Most participants (71%, n = 873) revealed that the routine vaccination plays an important role in protecting them and their children from infectious diseases. The confidence in routine vaccination after the COVID-19 pandemic didn’t change among 59% (n = 723), decreased in 22% (n = 261) and increased in 19% (n = 238) of the participants. The most common reason for the change in participants’ confidence (68%, n = 743) in routine vaccination after the COVID-19 pandemic was the fear of the impact of COVID-19 vaccine on the immune system or the body’s ability to respond correctly to routine vaccines. Conclusions We have showed that there is little change in the confidence of routine vaccination among people in Saudi Arabia compared to before the COVID-19 pandemic. Our study could shed light on the potential challenges and opportunities for promoting vaccine acceptance and uptake in a post-pandemic era.